Periocular Skin Warming Promotes Sleep Onset Through Heat Dissipation From Distal Skin in Patients With Insomnia Disorder - Ichiba, Tomohisa; Kawamura, Aoi; Nagao, Kentaro; Kurumai, Yuichi; Fujii, Akio; Yoshimura, Atsushi; Yoshiike, Takuya; Kuriyama, Kenichi (Frontiers in Psychiatry, 2022)
Study Objectives: Periocular skin warming before bedtime has been demonstrated to improve subjective sleep initiation in healthy adults with mild sleep difficulty. This study aimed to investigate the effects of periocular skin warming on sleep initiation and thermoregulation processes in patients with insomnia disorder. Methods: Participants included those with sleep difficulty (n = 22) and those with insomnia disorder (n = 16). Individuals from both groups were assessed at baseline (habitual sleep-wake schedule) and after two intervention conditions (use of a warming eye mask or a sham eye mask before habitual bedtime). The subjective and electroencephalographic sleep onset latency, along with proximal and distal skin temperature after periocular skin warming, were evaluated. Results: Periocular skin warming reduced both subjective and objective sleep onset latency in both groups. Foot temperature and foot-proximal temperature gradient after getting into bed increased with periocular skin warming in both groups. However, the increase in hand temperature was observed only in the insomnia disorder group. Periocular skin warming also increased cardiac parasympathetic nervous activity in both groups. The reduction of objective sleep onset latency was strongly associated with heat dissipation from the foot skin region. Conclusions: These results suggest that periocular skin warming promotes sleep initiation by enhancing heat dissipation from the distal skin regions in individuals with sleep difficulty and insomnia disorder. Periocular skin warming could thus be a novel non-pharmacological therapy for insomnia disorder.